Knee OUTcome Study: A Comparison of the Patient Perceived Outcome between High Tibial Osteotomy, Unicompartmental and Total Knee Arthroplasty for Medial Compartment Osteoarthitis in Men under age 55. Issue 5 (31st May 2017) - Maxwell, Rod; Johnston, Andy; Lees, David; Walker, Cameron
Objectives: Managing medial compartment osteoarthritis (OA) in the younger male patient is challenging because these patients tend to be physically high demand. Traditionally, High Tibial Osteotomy (HTO) has been the favoured surgical option, but Total (TKA) and Unicompartmental (UKA) knee arthroplasty have been more recently utilized. Our aims were to compare patient reported outcome, revision and reoperation rates with these 3 procedures. Methods: Using our hospital data bases we retrieved the details of male patients under 55 who had one of the 3 procedures performed between 2005-2013, for medial compartment OA by 6 knee surgeons in our group. All 6 surgeons used the 3 procedures in this cohort. The TKA database was analysed to exclude patients who did not meet the criteria for HTO/UKA of isolated medial OA. The 3 groups had their satisfaction assessed retrospectively using the Forgotten Joint Score (FJS), information on occupation, reoperation and duration of satisfaction were also questioned. Hospital records were reviewed for the reoperation and revision rate on all of the patients identified. Results: We identified 117 TKA in patients under 55, 27 TKA which met our criteria, 75 HTO (medial opening wedge) and 95 UKA (Oxford cementless). The mean followup periods for HTO/UKA/TKA were 8.1, 6.1, 7.5 years respectively. Of the HTO group, 19 (25%) were revised to TKA at a mean 4.8 years, 8 underwent reoperation for mal/nonunion, and 10 had reoperation for fixation issues. Overall a reoperation rate of 50% and projected 10 year survivorship of 58% for HTO. Of the UKA group, there was 1 revision to TKA at 1 year for tibial component loosening and 3 reoperations for bearing instability, retaining the primary implant. Reoperation rate 4% and projected 10 year survivorship 99%. Of the TKA group there were 2 revisions at 4 years for tibial component loosening, no non-revision reoperations, reoperation rate 7.5% with projected 10 year survivorship 92.5%. The Forgotten Joint Score results (0-100) were median 21 for HTO, 38 for TKA, 67 for UKA. All comparisons between the three groups were significant. TKA vs HTO p value 0.04 (CI 0.67-36.54), UKA vs TKA p value 0.02 (CI 2.26-35.58), UKA vs HTO p value 0.00001 (CI 25.36-49.68). Further analysis of the HTO cohort revealed that 75% of the unrevised cases considered the benefit of the index procedure had expired at a mean 3.1 years, yet they had not sought further surgery, despite a mean FJS of only 18 in this subgroup. Conclusion: In this retrospective cohort study with medium term followup of 3 procedures performed by 6 knee surgeons, patients were highly matched by virtue of gender (male), age (<55 years), activity level (Tegner scores), pathology (isolated medial compartment OA). Regarding survivorship of the index procedure, the outcome for Osteotomy was poor with 58% at 10 yrs and high reoperation/complication rate of 50% at mean 4.8 years. The best survivorship/reoperation rates were in the UKA group (99% and 4% respectively). Regarding patient reported outcome using Forgotten Joint Score, comparison between all groups favoured UKA. The comparison between UKA and Osteotomy was so powerful, as to render the p value almost unmeasureable (0.00001). Unrevised Osteotomy patients reported disappointing duration of benefit (mean 3.1 years), and low FJS (mean 18), but hadn't sought further surgery. A further example that revision rates are not a good indicator of outcome, especially for Osteotomy. Our study demonstrates that at medium term followup, cementless Oxford UKA provides the best outcome with respect to patient satisfaction, function and survivorship compared to Osteotomy and TKA in men under 55 yrs with medial compartment osteoarthritis.